2011
DOI: 10.1007/s00464-011-1739-5
|View full text |Cite
|
Sign up to set email alerts
|

Internal hernia after laparoscopic gastric resection with antecolic Roux-en-Y reconstruction for gastric cancer

Abstract: Background To decrease the incidence of internal hernia after laparoscopic gastric bypass, current recommendations include closure of mesenteric defects. Laparoscopic gastric resection is used increasingly for the treatment of gastric cancer, but the incidence of internal hernia in the treated patients has not been studied. Methods This study retrospectively reviewed 173 patients who underwent laparoscopic resection for gastric cancer at one institution, including distal and total gastric resections with antec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Hosoya et al [11] first reported internal herniation after laparoscopy-assisted gastrectomy with gastric cancer patients. In their report, they experienced 4 (7 %) jejunojejunal hernias among 58 patients whose jejunojejunal mesenteric defect was not closed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hosoya et al [11] first reported internal herniation after laparoscopy-assisted gastrectomy with gastric cancer patients. In their report, they experienced 4 (7 %) jejunojejunal hernias among 58 patients whose jejunojejunal mesenteric defect was not closed.…”
Section: Resultsmentioning
confidence: 99%
“…In the recent widespread use of laparoscopic surgery for gastric cancer, we should be aware of internal hernia after distal gastrectomy. However, there are only a few reports on the incidence of internal hernia, especially Petersen's hernia, with R-Y reconstruction after laparoscopic distal gastrectomy for cancer [11,12]. This is a matter of concern because these hernias can present dramatically as an acute bowel obstruction with necrosis of the bowel, especially when diagnosis with prompt surgical intervention is delayed [9].…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Recently, many authors prefer the anticolic route for the Roux limb, which reduces the potential sites for hernia from three to two, and close the mesenteric defect after a laparoscopic Roux-en-Y gastric bypass. In our early period of TLTG, 4 cases had an internal herniation after the operation because we did not close all of the defect.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that the long-term results of laparoscopic surgery and open surgery in gastric cancers were similar (5,8). Roux-en-Y reconstruction is frequently preferred because of its prevention of anastomotic leaks and reflux in laparoscopic total or subtotal gastrectomy (9). Following Roux-en-Y reconstruction, Petersen's spaces, jejuna-jejunal spaces, and transverse mesocolon spaces (if anastomosis was performed retrocolic) was formed.…”
Section: Discussionmentioning
confidence: 99%